A method for manufacturing a high-performance high-pressure oil pipe
Patent Information
- Application Number
- CN202611333472.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-20
AI Technical Summary
[0002]在内燃机超高压共轨燃油喷射系统以及腐蚀性较强的流体输送管路中,高压油管长期承受高频交变脉动载荷,同时还受到含氯、酸性多元燃油介质的强腐蚀作用,超级奥氏体耐蚀不锈钢含有较高比例的铬、镍、钼等合金元素,具有良好的耐点蚀和耐缝隙腐蚀性能,成为制造厚壁小口径高压油管的重要材料,此类合金中钼、铬含量较高,在600℃至1000℃的敏化温度区间内,容易析出金属间相,传统的高温长时间固溶处理虽然能够消除析出相,但长时间高温保温容易使奥氏体晶粒明显粗化,从而降低材料的屈服强度和高周疲劳极限,为了减少析出相并抑制晶粒长大,现有技术通常采用高频感应快速升温和快速淬冷工艺,但是,高频感应加热存在明显的电磁趋肤效应,对于厚壁小口径管材,容易形成外壁温度高、内壁温度低的径向温度梯度,使管壁内表面的升温明显滞后于外表面
1、在高性能高压油管用钢管的制备中,通过对热加工过程进行合理控制,可减少铬、钼等合金元素在奥氏体晶界附近的偏聚,降低金属间相形核和析出的可能,使管坯在高温塑性变形过程中保持较均匀的单相固溶组织,由此能够减少脆性析出相造成的局部应力集中和热加工开裂,使热成型后的管坯晶粒较为均匀、组织更加致密,为后续冷变形提供兼具塑性和韧性的基体。
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing high-performance high-pressure oil pipes, belonging to the field of metal material plastic processing and heat treatment technology. Background Technology
[0002] In ultra-high pressure common rail fuel injection systems of internal combustion engines and in highly corrosive fluid transport pipelines, high-pressure fuel lines are subjected to high-frequency alternating pulsating loads for extended periods, while also experiencing strong corrosion from chlorine-containing and acidic multi-element fuel media. Super austenitic corrosion-resistant stainless steel, containing a high proportion of alloying elements such as chromium, nickel, and molybdenum, exhibits excellent resistance to pitting and crevice corrosion, making it an important material for manufacturing thick-walled, small-diameter high-pressure fuel lines. This type of alloy has a high molybdenum and chromium content, and within the sensitization temperature range of 600℃ to 1000℃, it readily precipitates intermetallic deposits. While traditional high-temperature, long-term solution treatment can eliminate precipitated phases, prolonged high-temperature holding can easily cause significant coarsening of austenite grains, thereby reducing the yield strength and high-cycle fatigue limit of the material. In order to reduce precipitated phases and inhibit grain growth, existing technologies usually employ high-frequency induction heating and rapid quenching processes. However, high-frequency induction heating has a significant electromagnetic skin effect. For thick-walled, small-diameter pipes, it is easy to form a radial temperature gradient with a high outer wall temperature and a low inner wall temperature, causing the heating of the inner surface of the pipe wall to lag significantly behind that of the outer surface.
[0003] In the subsequent cooling process, to avoid bending deformation of the pipe, conventional processes typically employ symmetrical cooling of the inner bore and outer wall with the same strength. Because the outer wall temperature is higher, its cooling and contraction lag behind the inner wall. Thus, the outer layer, during its later contraction, exerts a stretching effect on the already cooled inner layer, ultimately leaving residual tensile stress on the inner surface of the steel pipe. Under the continuous impact of high-pressure pulsating fuel, this residual tensile stress can easily become a hidden danger for microcrack initiation and intergranular corrosion. For example, Chinese invention patent application CN104826890A discloses a manufacturing method for super austenitic stainless steel seamless pipes. The method controls the forming process of seamless tubes by setting fixed induction heating temperatures in stages and discrete deformation parameters for each pass. However, under complex continuous processing conditions such as variable wall thickness or large strain, this method essentially relies on preset static step parameters, which is difficult to cope with the nonlinear strong coupling evolution between the transient temperature drop, dynamic phase transformation and deformation resistance of super austenitic stainless steel during severe plastic deformation. Due to the lack of active coordinated control over the instantaneous load and temperature evolution in the deformation zone, it is very easy to induce grain boundary tearing or promote the precipitation of brittle phases in local stress concentration areas, and it is impossible to balance forming efficiency and finished product microstructure stability.
[0004] Therefore, the technical problem to be solved by this invention is how to block the precipitation of brittle phases between metals and inhibit the coarsening of austenite grains during the processing of super austenitic corrosion-resistant stainless steel high-pressure oil pipes, eliminate the residual tensile stress on the inner surface caused by the temperature gradient of the pipe wall section, and prepare finished steel pipes with high pressure resistance, resistance to alternating pulsating fatigue and resistance to local corrosion. Summary of the Invention
[0005] To address the problems in the background art, the technical solution of the present invention is as follows: A method for preparing a high-performance high-pressure oil pipe steel tube, comprising the following steps: Step S1: Perform warm rolling and cold drawing stepwise plastic deformation on the super austenitic corrosion-resistant stainless steel rough tube, control the cumulative true strain to be not less than 0.85, construct a deformation hardening structure inside the tube wall, and obtain the deformed steel tube. Step S2: The deformed steel pipe is fed into an induction heating coil and heated to the target solution temperature of 1120°C to 1160°C at a heating rate of 120°C / s to 200°C / s. The axial online moving temperature uniformity time at the target solution temperature is 8s to 15s, so that the carbides and metal phases dissolve into the austenitic matrix. Step S3: The steel pipe leaving the induction heating coil is introduced into the gas-water atomization cooling zone. Based on the radial temperature difference between the outer wall temperature and the inner wall temperature after induction heating, a gas-water mixed medium is simultaneously sprayed into the inner hole and the outer wall of the steel pipe to carry out asymmetric quenching. The pressure of the medium sprayed into the inner hole and the water-gas mass ratio are controlled to be higher than the pressure of the medium sprayed onto the outer wall, so that the cooling rate of the inner wall surface is higher than the cooling rate of the outer wall, and the average cooling rate of the whole to below 400℃ is not less than 180℃ / s. A residual compressive stress layer is formed on the inner hole surface by applying radial extrusion to the inner wall through the late thermal contraction of the outer wall. Step S4 involves performing cold reduction and sizing calibration on the quenched steel pipe and pulse electrochemical polishing on the inner hole of the steel pipe to remove the cold-worked hardened and modified layer on the surface of the inner hole and eliminate micro-defects on the inner surface.
[0006] Preferably, the total reduction of area of the stepped plastic deformation in step S1 is 65% to 85%, and includes the following sub-processes: Step S11, preheating the super austenitic corrosion-resistant stainless steel blank to 280°C to 350°C and performing two-roll cyclic warm rolling, with a reduction of area of 35% to 45%; Step S12, performing surface pickling, phosphating and saponification lubrication treatment on the warm-rolled steel pipe; Step S13, performing 2 to 3 passes of floating mandrel cold drawing at room temperature, with the reduction of area per pass controlled at 18% to 25%, forming interwoven dislocation slip bands inside the pipe wall.
[0007] Preferably, before step S1, there are also a billet casting and rough tube preparation process: the alloy ingot is cast using a dual process of vacuum induction melting and electroslag remelting; the alloy ingot is heated to 1200°C to 1240°C and held for 45 min to 60 min to perform high-temperature homogenization treatment; then it is water quenched to room temperature at a cooling rate of not less than 50°C / s, and hot extrusion piercing is used to produce super austenitic corrosion-resistant stainless steel rough tube.
[0008] Preferably, in step S2, the steel pipe passes through the induction heating coil at a uniform axial moving speed of 0.15 m / s. After solution treatment, the average grain size of recrystallization inside the austenitic matrix is controlled to be between 7.5 μm and 12.0 μm, corresponding to a grain size of ASTM grade 10.0 to 11.5.
[0009] Preferably, the process parameters for asymmetric quenching in step S3 are as follows: the injection pressure of the cooling medium injected into the inner hole is 1.5 MPa, and the water-to-air mass ratio is 1:3; the injection pressure of the cooling medium injected towards the outer wall is 0.8 MPa, and the water-to-air mass ratio is 1:5; and the injection directions of the cooling medium injected towards the inner hole and the outer wall are both reverse injection at an angle of 45° to 60° with the axial movement direction of the steel pipe.
[0010] Preferably, after processing in steps S2 and S3, the lattice of overlapping positions in the microstructure of the steel pipe The proportion of grain boundaries to the total grain boundary length is not less than 65%, and a residual compressive stress layer is formed on the surface of the inner hole of the steel pipe.
[0011] Preferably, in step S4, the cold reduction and sizing dimension calibration is performed using a three-roll planetary mill, with the outer diameter reduction controlled at 0.5% to 1.2%; the pulse electrochemical polishing uses a mixed electrolyte of phosphoric acid and sulfuric acid to remove the surface layer of the inner hole of the steel pipe with a single-sided thickness of 15μm to 25μm.
[0012] Preferably, after step S4, the surface roughness of the inner hole of the steel pipe is... The residual stress on the inner wall is not greater than 0.15 μm, and the residual stress is either under compressive stress or under tensile stress with a value not greater than 30 MPa. The critical pitting temperature measured according to ASTM G48 Method A is not lower than 76 °C.
[0013] Preferably, the room temperature yield strength of the finished steel pipe is... It can withstand 10,000,000 cycles of pulsating fatigue load with an alternating internal pressure of 0 to 300 MPa and a frequency of 20 Hz without cracking or leakage, and the hydraulic burst pressure is not less than 650 MPa.
[0014] Compared with the prior art, the beneficial effects of the present invention are: 1. In the preparation of high-performance high-pressure oil pipe steel, by reasonably controlling the hot working process, the segregation of alloying elements such as chromium and molybdenum near the austenite grain boundaries can be reduced, the possibility of intermetallic phase nucleation and precipitation can be reduced, and the billet can maintain a relatively uniform single-phase solid solution structure during high-temperature plastic deformation. This can reduce local stress concentration and hot working cracking caused by brittle precipitates, and make the hot-formed billet grains more uniform and the structure more compact, providing a matrix with both plasticity and toughness for subsequent cold deformation.
[0015] 2. By rationally controlling the deformation amount and deformation rate during multi-pass cold drawing, the dislocation slip and deformation twinning within the austenite grains can be more coordinated, reducing local strain concentration that is prone to occur during large deformation and inhibiting the initiation of micropores at grain boundaries. This is beneficial for uniformly reducing the wall thickness of the steel pipe, maintaining relatively uniform circumferential deformation, improving the plastic flow state of the inner and outer walls, thereby reducing the dispersion of dimensional tolerances of the finished steel pipe, and making the residual stress distribution of the pipe wall more gradual, better adapting to the requirements of high-pressure fluid pulsating loads on dimensional accuracy and microstructure uniformity.
[0016] 3. By combining solution heat treatment with rapid cooling, alloying elements can be fully dissolved in the austenitic matrix, reducing chromium- and molybdenum-depleted areas near grain boundaries and decreasing the likelihood of localized corrosion preferentially occurring at grain boundaries. At the same time, it is beneficial to form a more uniform and stable single-phase austenitic structure, maintain the continuity of the surface passivation film, reduce residual stress and intergranular sensitization tendency, thereby improving the finished steel pipe's resistance to intergranular corrosion and pitting corrosion, and reducing selective dissolution of grain boundaries under the long-term action of high-pressure fuel oil and chemical media. Attached Figure Description
[0017] Figure 1 This is a flowchart illustrating the steps involved in manufacturing the steel pipe for the high-pressure oil pipe of the present invention. Figure 2 This is a diagram illustrating the evolution of the steel pipe structure and the construction of residual compressive stress on the inner wall, as presented in this invention.
[0018] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0019] The technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application are within the scope of protection of this application.
[0020] A method for manufacturing a high-performance high-pressure oil pipe includes the following steps: Step S1: Perform warm rolling and cold drawing stepwise plastic deformation on the super austenitic corrosion-resistant stainless steel rough tube, control the cumulative true strain to be not less than 0.85, construct a deformation hardening structure inside the tube wall, and obtain the deformed steel tube. Step S2: The deformed steel pipe is fed into an induction heating coil and heated to the target solution temperature of 1120°C to 1160°C at a heating rate of 120°C / s to 200°C / s. The axial online moving temperature uniformity time at the target solution temperature is 8s to 15s, so that the carbides and metal phases dissolve into the austenitic matrix. Step S3: The steel pipe leaving the induction heating coil is introduced into the gas-water atomization cooling zone. Based on the radial temperature difference between the outer wall temperature and the inner wall temperature after induction heating, a gas-water mixed medium is simultaneously sprayed into the inner hole and the outer wall of the steel pipe to carry out asymmetric quenching. The pressure of the medium sprayed into the inner hole and the water-gas mass ratio are controlled to be higher than the pressure of the medium sprayed onto the outer wall, so that the cooling rate of the inner wall surface is higher than the cooling rate of the outer wall, and the average cooling rate of the whole to below 400℃ is not less than 180℃ / s. A residual compressive stress layer is formed on the inner hole surface by applying radial extrusion to the inner wall through the late thermal contraction of the outer wall. Step S4 involves performing cold reduction and sizing calibration on the quenched steel pipe and pulse electrochemical polishing on the inner hole of the steel pipe to remove the cold-worked hardened and modified layer on the surface of the inner hole and eliminate micro-defects on the inner surface.
[0021] Preferably, the total reduction of area of the stepped plastic deformation in step S1 is 65% to 85%, and includes the following sub-processes: Step S11, preheating the super austenitic corrosion-resistant stainless steel blank to 280°C to 350°C and performing two-roll cyclic warm rolling, with a reduction of area of 35% to 45%; Step S12, performing surface pickling, phosphating and saponification lubrication treatment on the warm-rolled steel pipe; Step S13, performing 2 to 3 passes of floating mandrel cold drawing at room temperature, with the reduction of area per pass controlled at 18% to 25%, forming interwoven dislocation slip bands inside the pipe wall.
[0022] Preferably, before step S1, there are also a billet casting and rough tube preparation process: the alloy ingot is cast using a dual process of vacuum induction melting and electroslag remelting; the alloy ingot is heated to 1200°C to 1240°C and held for 45 min to 60 min to perform high-temperature homogenization treatment; then it is water quenched to room temperature at a cooling rate of not less than 50°C / s, and hot extrusion piercing is used to produce super austenitic corrosion-resistant stainless steel rough tube.
[0023] Preferably, in step S2, the steel pipe passes through the induction heating coil at a uniform axial moving speed of 0.15 m / s. After solution treatment, the average grain size of recrystallization inside the austenitic matrix is controlled to be between 7.5 μm and 12.0 μm, corresponding to a grain size of ASTM grade 10.0 to 11.5.
[0024] Preferably, the process parameters for asymmetric quenching in step S3 are as follows: the injection pressure of the cooling medium injected into the inner hole is 1.5 MPa, and the water-to-air mass ratio is 1:3; the injection pressure of the cooling medium injected towards the outer wall is 0.8 MPa, and the water-to-air mass ratio is 1:5; and the injection directions of the cooling medium injected towards the inner hole and the outer wall are both reverse injection at an angle of 45° to 60° with the axial movement direction of the steel pipe.
[0025] Preferably, after processing in steps S2 and S3, the lattice of overlapping positions in the microstructure of the steel pipe The proportion of grain boundaries to the total grain boundary length is not less than 65%, and a residual compressive stress layer is formed on the surface of the inner hole of the steel pipe.
[0026] Preferably, in step S4, the cold reduction and sizing dimension calibration is performed using a three-roll planetary mill, with the outer diameter reduction controlled at 0.5% to 1.2%; the pulse electrochemical polishing uses a mixed electrolyte of phosphoric acid and sulfuric acid to remove the surface layer of the inner hole of the steel pipe with a single-sided thickness of 15μm to 25μm.
[0027] Preferably, after step S4, the surface roughness of the inner hole of the steel pipe is... The residual stress on the inner wall is not greater than 0.15 μm, and the residual stress is either under compressive stress or under tensile stress with a value not greater than 30 MPa. The critical pitting temperature measured according to ASTM G48 Method A is not lower than 76 °C.
[0028] Preferably, the room temperature yield strength of the finished steel pipe is... It can withstand 10,000,000 cycles of pulsating fatigue load with an alternating internal pressure of 0 to 300 MPa and a frequency of 20 Hz without cracking or leakage, and the hydraulic burst pressure is not less than 650 MPa.
[0029] Example 1: The steel pipe prepared in this example is used in the ultra-high pressure common rail fuel injection system of an internal combustion engine with a working pressure of over 250 MPa. The fuel medium has multi-element acidity and chlorine-containing corrosion characteristics. A thick-walled, small-diameter super austenitic corrosion-resistant stainless steel pipe with an outer diameter of 6.35 mm, an inner diameter of 3.00 mm, and a wall thickness of 1.675 mm was selected as the preparation object. The alloy ingot was smelted using a combination of vacuum induction melting and electroslag remelting. The chemical composition, by mass percentage, includes: C 0.014%, Si 0.32%, Mn 1.15%, P 0.015%, S 0.002%, Cr 25.20%, Ni 22.10%, Mo 6.45%, N 0.24%, Cu 0.85%, with the balance being Fe and unavoidable impurities. Based on the pitting resistance equivalent formula... The calculated pitting corrosion resistance equivalent of this super austenitic corrosion-resistant stainless steel is 50.33, of which... Indicates pitting resistance equivalent. , , The numbers represent the mass percentage content of chromium, molybdenum, and nitrogen in the alloy matrix, respectively. The forged round billet is fed into a heating furnace and heated to 1220℃ and held for 50 min to eliminate dendritic segregation of molybdenum and chromium. Then, it is water quenched to room temperature at a cooling rate of more than 50℃ / s and hot extrusion piercing to produce an initial rough tube with an outer diameter of 25 mm and a wall thickness of 3.5 mm.
[0030] To reduce the work hardening rate of super austenitic corrosion-resistant stainless steel due to low stacking fault energy, and to simultaneously construct a strain-hardening structure with high-density distortion energy within the tube wall, the initial rough tube is preheated to 320℃ using an induction coil. Under temperature conditions avoiding the dynamic strain aging embrittlement range, it is fed into a two-roll periodic cold rolling mill for single-pass warm rolling. The reduction of area is controlled at 42.5%, reducing the rough tube's diameter and wall thickness to a warm-rolled tube with an outer diameter of 16mm and a wall thickness of 2.2mm. This process forms interwoven dislocation slip bands and a high-density dislocation entanglement structure within the grains. Warm rolling and subsequent cold drawing together constitute a stepped plastic deformation process, with the total reduction of area controlled between 65% and 85%, accumulating true strain... The calculation is based on the change in cross-sectional area before and after each plastic deformation pass. Specifically, the natural logarithm of the ratio of the cross-sectional area before deformation to the cross-sectional area after deformation in each pass is taken to obtain the true strain for that pass. The true strain of the warm rolling pass and each cold drawing pass are then added together. When the cumulative true strain reaches 0.85 or higher, a high-density interlocking dislocation entanglement with a density higher than 10 to the power of 15 per square meter is formed inside the tube wall cross-section, providing deformation energy storage for subsequent rapid recrystallization. The warm-rolled tube is sequentially immersed in a mixed pickling solution of nitric acid and hydrofluoric acid, a phosphate solution, and a sodium stearate saponification solution to complete surface pickling, phosphating, and saponification lubrication treatment. Subsequently, two cold drawing processes are performed at room temperature using a floating mandrel. The first cold drawing is to an outer diameter of 10.0 mm and a wall thickness of 1.9 mm, and the second cold drawing is to an outer diameter of 6.45 mm and a wall thickness of 1.68 mm, thus accumulating the true strain. Reached 0.92, of which This represents the cumulative true strain of the stepped plastic deformation caused by warm rolling and cold drawing. Through the aforementioned stepped plastic deformation caused by warm rolling and cold drawing, the stored plastic deformation energy is distributed in the lattice distortion region of each layer of the tube wall cross section.
[0031] The cold-drawn steel pipe is fed into an induction heating coil at a constant axial speed of 0.15 m / s. This coil employs a multi-stage high-frequency electromagnetic induction structure, applying high-frequency induced eddy currents to cause the steel pipe to traverse the 600°C to 1000°C intermetallic brittle phase precipitation temperature range at a heating rate of 160°C / s, directly reaching the target solution temperature of 1140°C. The induction heating coil is arranged with three sets of heating modules and five sets of temperature-maintaining modules along its axial direction, with a total effective induction heating zone length of 1.5 m. When the steel pipe passes through at a constant speed of 0.15 m / s, it completes rapid heating within the first 0.3 m of the heating modules in 2 seconds. The tube then moves smoothly through the temperature equalization module for 10 seconds within a 1.2m range. The temperature equalization module is equipped with an insulating quartz ceramic jacket and an inert gas anti-oxidation curtain to reduce heat radiation and convection loss during the axial movement of the high-temperature tube, thus maintaining a stable energy distribution within the induction heating zone. The axial online temperature equalization time of the steel tube at the target solid solution temperature is 10 seconds, allowing the nanoscale carbides and intermetallic phases in the matrix to dissolve into the austenitic matrix. Simultaneously, the distortion energy accumulated from the previous cold working causes discontinuous static recrystallization inside the tube wall, with an average recrystallized grain size of 8.6μm, corresponding to a grain size of ASTM11. Grade 0 standard; During the axial online moving temperature equalization process from 8s to 15s, the induction heating coil adopts segmented power control. The front coil maintains a high-temperature solid solution range of 1140℃, while the rear equalization coil applies a 180kHz high-frequency auxiliary magnetic field. The skin heat energy generated by the high-frequency alternating magnetic field compensates for the heat loss from the outer wall to the environment, ensuring that the outer layer of the pipe wall continuously receives electromagnetic heat replenishment. The inner wall mainly absorbs heat through thermal conduction, maintaining a radial temperature difference of 120℃ to 150℃ higher on the outer wall than the inner wall across a 1.675mm pipe wall cross-section. The skin effect of high-frequency electromagnetic induction causes alternating eddy currents to concentrate and distribute on the outer layer of the pipe, thereby forming... The radial temperature difference between the outer wall temperature and the inner wall temperature serves as the temperature condition for subsequent asymmetric quenching. A colorimetric dual infrared thermometry and heat transfer numerical simulation collaborative monitoring system is configured at the outlet of the induction heating coil. The system collects the surface temperature data of the outer wall of the steel pipe in real time through a dual-wavelength infrared thermometer, and inputs the induction heating frequency of 350kHz, heating power and pipe movement speed into a pre-calibrated two-dimensional heat conduction finite element model of the pipe wall in real time. Based on the measured temperature of the outer wall and the heat conduction model, the radial temperature field distribution curve of the cross section from the outer wall to the inner wall is calculated online to obtain the real-time temperature of the inner wall surface and the radial temperature difference data of 120℃ to 150℃ between the inside and outside of the pipe wall.
[0032] After the steel pipe reaches a homogeneous solution-heated state and is removed from the induction heating coil, it is introduced into a coaxially arranged air-water atomization cooling zone. This zone is equipped with a multi-channel supercritical air-water mixing directional atomization quenching device. Based on the deformation energy accumulated during the previous cold drawing and the radial temperature difference formed by induction heating, asymmetric quenching is achieved by simultaneously spraying air-water mixed media with different parameters onto the inner hole and outer wall of the steel pipe. For a steel pipe with an inner diameter of 3.00 mm, a heat-resistant alloy hollow spray gun with an outer diameter of 1.80 mm and a closed front end is coaxially suspended inside the quenching device. The hollow spray gun has 0.25 mm diameter backward-sloping micro-orifice nozzles evenly distributed along its circumference. The air-water mixed media passes through the internal channels of the hollow spray gun and... The oblique micro-orifice nozzle sprays high-speed onto the inner wall of the tube. The resulting gas and water waste phases are discharged along the 1.20mm annular gap between the outer wall of the hollow spray gun and the inner hole of the steel pipe, in the opposite direction to the pipe's movement. This maintains continuous high-pressure medium injection and discharge within the micro-cavity. The cooling medium injected into the inner hole of the steel pipe has a pressure of 1.5MPa and a water-to-gas mass ratio of 1:3, while the cooling medium injected onto the outer wall of the steel pipe has a pressure of 0.8MPa and a water-to-gas mass ratio of 1:5. The jetting directions of both the inner and outer wall atomizing nozzles are at a 50° angle to the axial movement direction of the steel pipe, spraying in the opposite direction. The tangential shearing action of the atomized fluid strips away the vapor film generated on the inner wall, resulting in a higher cooling rate on the inner wall surface compared to the outer wall surface. The hollow spray gun extending into the inner hole uses a circumferential swirling micro-orifice nozzle. The nozzle outlet section forms a 50° counter-current angle with the pipe axis and is tangentially deflected by 15°. Under conditions of 1.5MPa pressure and a water-to-gas mass ratio of 1:3, the gas-water two-phase atomized fluid forms a spiral-wound, wall-attached flow field on the 3.00mm inner hole wall at a velocity exceeding 120m / s. The tangential kinetic energy of the fluid is converted into shear stress on the vapor film on the inner wall, overcoming the surface tension barrier of film boiling, tearing and peeling off the gas film, allowing the cooling medium to directly contact the high-temperature metal inner wall, and changing the heat transfer mode from film boiling to cavitation boiling. The steel pipe cools from 1140℃ to 380℃ in 3.8s, and the overall temperature drops to below 400℃ on average. However, the cooling rate reaches 200℃ / s, quickly surpassing the nose-tip temperature zone for brittle phase precipitation in the intermetallic region. The inner wall surface, due to its lower temperature and higher cooling rate, undergoes volume shrinkage and solidification first. Subsequently, the outer wall, during late-stage thermal shrinkage, continuously applies circumferential and radial mechanical compression to the already solidified inner wall, forming a residual compressive stress layer on the surface of the steel pipe's inner bore. The asymmetric quenching process parameters were calibrated through gas-liquid two-phase thermal flow field simulation and gradient parameter comparison experiments: when the inner bore injection pressure is below 1.0 MPa or the water-to-gas mass ratio is below 1:4, the inner bore cooling rate drops below 150℃ / s, and the inner wall cannot solidify earlier than the outer wall; the residual stress on the inner surface transforms into tensile stress. When the outer wall injection pressure is above 1...When the pressure is 2 MPa or the water-to-gas mass ratio is higher than 1:3, the outer wall cools and contracts too quickly, causing circumferential bending deformation of the tube. When the jet angle is controlled between 45° and 60° for reverse injection, the residence time of the gas-water medium in the inner hole matches the impact scouring kinetic energy, resulting in a residual compressive stress of -150 MPa to -200 MPa on the inner hole surface.
[0033] After quenching, the steel pipes were calibrated using a three-roll planetary mill under micro-tension conditions through cold reduction and sizing. The outer diameter reduction was controlled at 0.8%, calibrating the outer diameter of the steel pipe to a tolerance range of 6.35 mm. During the cold reduction and sizing process, the three-roll planetary mill applied a slight reduction of 0.8% to the outer wall of the steel pipe. The stress transfer across the pipe wall cross-section resulted in a work-hardened altered layer with a thickness of approximately 3 μm on the inner surface. The effective depth of the residual compressive stress layer formed by asymmetric quenching reached 150 μm to 200 μm, with the maximum compressive stress peak located 25 μm to 50 μm from the inner surface. In the subsurface region of m, pulsed electrochemical polishing removes the 20μm cold-worked modified layer and drawing micro-scratches from the inner surface through anodic dissolution. The removal depth does not reach the area where the residual compressive stress peak of the subsurface layer is located. Simultaneously, it removes stress concentration areas at the outermost micro-defects, ensuring a relatively uniform residual compressive stress state on the newly formed inner hole surface. Subsequently, a mixed electrolyte of phosphoric acid and sulfuric acid is introduced into the steel pipe's inner hole for continuous pulsed electrochemical polishing. Anodic dissolution removes the 20μm thick cold-worked modified layer from the inner hole surface, eliminating drawing scratches and localized defects, resulting in a final steel pipe inner hole surface roughness of [missing information]. The microstructure reached 0.11 μm, and the surface layer of the inner pore maintained a stable residual compressive stress state; electron backscatter diffraction and scanning electron microscopy microstructure analysis revealed low-energy coincident sites in the crystalline structure of the steel tube. Grain boundaries account for 68.5% of the total grain boundary length, disrupting the continuous, random, large-angle grain boundary network within the austenitic matrix; overlapping position lattice The grain boundary ratio threshold was determined based on the crystallographic mechanism of low-energy phase boundary corrosion inhibition and fatigue propagation, and comparative testing, using the lattice of overlapping low-energy points. Grain boundary interface energy is only 10% of that of ordinary random large-angle grain boundaries, when the lattice at the overlapping position... When grain boundaries account for more than 65% of the total grain boundary length, a continuous, low-energy grain boundary network barrier is formed in three-dimensional space, blocking the segregation of sensitizing elements and the penetration of chlorine-containing media along the grain boundaries; experiments show that when the lattice of overlapping positions... When the grain boundary ratio is below 65%, the random large-angle grain boundary network reconnects, the critical pitting temperature drops below 70℃, the high-frequency pulsating fatigue life decreases by more than 50%, and the specified plastic elongation strength of the finished steel pipe at room temperature... The tensile strength is 545 MPa. The strength is 875 MPa, and the elongation after fracture is... The measured hydraulic burst pressure reached 662 MPa, with a strength of 43.5%. Under fatigue test conditions with alternating internal pressure from 0 to 300 MPa and a pulsation frequency of 20 Hz, it withstood... No cracking or leakage was observed during the second pulsation cycle. At the same time, the critical pitting temperature measured according to ASTM G48 standard method A reached 78°C, which ensured that the high-pressure pulsation fatigue resistance and medium corrosion resistance simultaneously met the service requirements of the ultra-high pressure common rail system.
[0034] Example 2: This example uses the same batch of super austenitic corrosion-resistant stainless steel ingots to conduct comparative experiments on the parameter combinations of warm rolling and cold drawing graded plastic deformation, high-frequency electromagnetic induction solution treatment, and asymmetric quenching. The aim is to observe the phase transformation kinetics response, crystal structure changes, and pressure-bearing performance of small-diameter thick-walled pipe fittings in high-pressure common rail systems. The ingots are prepared using a dual process of vacuum induction melting and electroslag remelting. By mass percentage, the matrix composition is: C 0.014%, Si 0.32%, Mn 1.15%, P 0.015%, S 0.002%, Cr 25.20%, Ni 22.10%, Mo 6.45%, N 0.24%, Cu 0.85%, with the balance being Fe and unavoidable impurities. After homogenization treatment and hot extrusion, the ingots are produced with an outer diameter of 25 μm. The initial rough tube, with a diameter of m and a wall thickness of 3.5 mm, was used in the test platform equipped with an electromagnetic induction heating unit capable of multi-segment zone temperature control. The thermocouple response time was less than 0.05 s, and the temperature control accuracy reached ±3℃. A water-air atomization cooling zone was set up adjacent to the outlet of the heating unit, within which a ring-shaped multi-nozzle supercritical water-air atomization spray gun assembly was coaxially installed. Servo pressure regulating valves and electromagnetic flow meters were respectively installed in the water and air supply lines of the inner bore and outer wall. The water-air medium mixing pressure control accuracy reached ±0.02 MPa. Mechanical and service performance testing was conducted using a high-frequency electro-hydraulic servo pulsating fatigue testing machine. The working pressure adjustment range was 0 to 400 MPa, the pulsation frequency response range was 10 Hz to 50 Hz, and the pressure fluctuation was controlled within ±1 MPa. The residual stress on the inner surface was measured using an X-ray stress analyzer with a chromium target. Radiation source and austenite 220 diffraction plane, measurement uncertainty less than ±15 MPa; grain boundary topology and lattice of coincidence sites. The grain boundary ratio was determined using a field emission scanning electron microscope equipped with an electron backscatter diffraction probe, with a step size of 0.1 μm; the critical pitting temperature was tested by immersion in a 6% ferric chloride solution according to ASTM G48 Method A.
[0035] The high-frequency electromagnetic induction heating rate is controlled between 120℃ / s and 200℃ / s to balance the rapid passage through the 600℃ to 1000℃ sensitized precipitation zone with the thermal stress distribution of the tube wall cross section, and to allow nanoscale carbides and intermetallic phases to dissolve into the austenite matrix; the axial online moving temperature homogenization time is controlled between 8s and 15s to limit the continued growth of recrystallized grains, and asymmetric quenching is combined with the accumulated true strain from the preceding process. The deformation energy storage and radial temperature difference formed by induction heating set the cooling parameters for the inner and outer walls. The injection pressure and water-to-gas mass ratio of the inner wall are higher than those of the outer wall, so that the cooling rate of the inner wall surface is higher than that of the outer wall surface. The late thermal contraction of the outer wall is used to form a residual compressive stress layer on the inner wall surface. All test groups used the same batch of raw materials and were processed into finished pipes with an outer diameter of 6.35 mm and a wall thickness of 1.675 mm. Test groups 1 to 4 were set as parameter gradient sample groups. At the same time, control groups 1 to 6 were set up with missing key processes, changed cooling methods and parameters exceeding the limit range. The pulsating fatigue life comparison used an alternating internal pressure from 0 to 300 MPa. The fatigue performance of each group was recorded by the number of cycles under the upper limit pressure of 300 MPa.
[0036] During the stepped plastic deformation stage of warm rolling and cold drawing, the warm rolling temperatures of test groups 1 to 4 were 280℃, 320℃, 350℃ and 300℃ respectively, and the cumulative true strain was... The values were 0.85, 0.92, 0.98, and 0.88, respectively. Following this, a high-frequency electromagnetic induction solution treatment stage was initiated. The target solution temperatures for the four groups were 1120℃, 1140℃, 1160℃, and 1130℃, respectively. The axial online temperature uniformization times were 15s, 10s, 8s, and 12s, respectively. All four groups underwent asymmetric quenching in the air-water atomization cooling zone. The injection pressure of the cooling medium into the inner hole was 1.5MPa, with a water-to-air mass ratio of 1:3. The injection pressure of the cooling medium towards the outer wall was 0.8MPa, with a water-to-air mass ratio of 1:5. The resulting overall cooling rates were 182℃ / s, 200℃ / s, 225℃ / s, and 191℃ / s, respectively. After this treatment, no second phase precipitation was observed in any of the four groups. The average grain sizes were 11.6μm, 8.6μm, 7.8μm, and 9.5μm, respectively. The overlapping position lattice... The grain boundary ratios were 65.4%, 68.5%, 70.8%, and 66.8% respectively, and the residual stresses on the inner wall surface were -162 MPa, -185 MPa, -198 MPa, and -173 MPa respectively. The room temperature yield strength... The pressures were 524 MPa, 545 MPa, 568 MPa, and 536 MPa, respectively, and the critical pitting temperatures were 76.5℃, 78.4℃, 80.6℃, and 77.2℃, respectively. In the pulsating fatigue test, test groups 1 to 4 reached... Second-rate, Second-rate, Subsequent No damage occurred during any of the two processes. The gradual plastic deformation from warm rolling and cold drawing resulted in a work-hardened structure characterized by interwoven dislocation slip bands within the austenite matrix. During the short-term induction solution process, deformation energy storage drove the formation of dense annealed twins at the grain boundaries, with overlapping lattice points. The increase in grain boundaries disrupts the continuous, random, large-angle grain boundary diffusion channels, inhibiting the electrochemical preferential dissolution of chlorinated acid fuel media along the grain boundaries; asymmetric quenching causes the inner wall to cool and solidify before the outer wall, and the late thermal contraction of the outer wall applies radial compression to the inner wall, keeping the inner wall of each test group under compressive stress and reducing the amplitude of alternating tensile stress on the inner surface of the pipe under pulsating internal pressure.
[0037] To compare the effects of symmetrical cooling, control group 1 had its warm rolling temperature set at 320℃, and the accumulated true strain was calculated. The coefficient of performance was 0.92, the target solution temperature was 1140℃, the axial online moving temperature homogenization time was 10s, both the inner hole and the outer wall were symmetrically sprayed with a spray pressure of 1.0MPa and a water-to-gas mass ratio of 1:4, the overall cooling rate was 195℃ / s, no second phase precipitation was observed in this group, the average grain size was 8.7μm, and the lattice of overlapping positions was [not specified]. The grain boundary ratio is 67.2%, and the room temperature yield strength is... The stress was 542 MPa, and the critical pitting temperature was 77.8 °C. Due to the symmetrical cooling of the inner and outer walls, the radial temperature difference formed by induction heating caused the outer wall to cool and shrink later than the inner wall. This late shrinkage of the outer wall exerted a tensile effect on the already cooled inner layer, causing the residual stress on the inner wall surface to become +68 MPa. The pulsating fatigue test cycled to... At this time, cracks began to appear in a localized area of the inner hole.
[0038] Control group 2 eliminated warm rolling and only used room temperature cold deformation to accumulate true strain. The value was 0.88; the target solution temperature was 1140℃; the axial online moving temperature homogenization time was 10s; the asymmetric quenching still used an inner hole pressure of 1.5MPa and a water-to-air mass ratio of 1:3 and an outer wall pressure of 0.8MPa and a water-to-air mass ratio of 1:5; the overall cooling rate was 198℃ / s; no second phase precipitation was observed in this group; the average grain size was 13.5μm; and the lattice of overlapping positions was [not specified]. The grain boundary ratio is 43.8%, the residual stress on the inner wall surface is -155 MPa, and the room temperature yield strength is... The pressure is 478 MPa, the critical pitting temperature is 71.5℃, and the pulsating fatigue test cycle is up to... Localized cracking occurred at this time. After canceling the warm rolling, the single room temperature cold deformation caused localized strain concentration in the low stacking fault energy austenite, and the uniformly distributed interwoven dislocation slip band deformation hardening structure as seen in the test group was not formed. The lattice of overlapping positions after short-term solidification was also affected. The proportion of grain boundaries decreases accordingly.
[0039] Control group 3 also did not undergo warm rolling, accumulating true strain The concentration was 0.72. A solution treatment temperature of 1200℃ and a homogenization time of 900s were used. The solution was heated in a resistance furnace followed by water quenching. The overall cooling rate was 45℃ / s. A small amount of second-phase precipitation appeared at the grain boundaries of this group. The average grain size was 41.5μm. The lattice of the overlapping sites... The grain boundary ratio is 32.5%, the residual stress on the inner wall surface is +125 MPa, and the room temperature yield strength is... The pressure is 365 MPa, and the critical pitting temperature is 62.5℃; the pulsating fatigue test cycle is up to... Intergranular brittle fracture occurs at this time.
[0040] When comparing the lower limit of solution treatment temperature, the rolling temperature of control group 4 was 320℃, and the cumulative true strain was... The target solution temperature was reduced to 1080℃, the axial online temperature uniformization time was 15s, and the asymmetric quenching was performed using an inner hole pressure of 1.5MPa and a water-to-air ratio of 1:3 and an outer wall pressure of 0.8MPa and a water-to-air ratio of 1:5. The overall cooling rate was 196℃ / s, and after treatment, grain boundary dispersion precipitation occurred. Phase, with an average grain size of 6.8 μm, and overlapping lattice sites. The grain boundary ratio is 41.2%, the residual stress on the inner wall surface is -170 MPa, and the room temperature yield strength is... The pressure is 445 MPa, and the critical pitting temperature is 52.4 °C; the pulsating fatigue test cycle is up to... This leads to brittle fracture of the precipitated phase. As the solution temperature decreases, the intermetallic... The phases were not fully dissolved into the austenitic matrix and diffused along the grain boundaries. Local chromium depletion and stress concentration occurred in the vicinity of the phase boundaries, which corresponds to the decrease in the critical pitting temperature and fatigue life of this group.
[0041] When comparing the upper limit of solution treatment temperature, the rolling temperature of control group 5 was 320℃, and the cumulative true strain was... The value was 0.92, the target solution temperature was raised to 1220℃, the axial online moving temperature homogenization time was 10s, the asymmetric quenching used an inner hole pressure of 1.5MPa and a water-to-air mass ratio of 1:3 and an outer wall pressure of 0.8MPa and a water-to-air mass ratio of 1:5, the overall cooling rate was 202℃ / s, no second phase precipitation was observed in this group, but the average grain size increased to 38.6μm, and the lattice of overlapping sites... The grain boundary ratio is 48.5%, the residual stress on the inner wall surface is -140 MPa, and the room temperature yield strength is... The pressure is 375 MPa, and the critical pitting temperature is 73.2 °C; the pulsating fatigue test cycle is up to... Grain boundary fatigue spalling occurred at this time. Compared with test group 2, after the solution temperature increased, the recrystallized grains became significantly coarser, and the room temperature yield strength decreased accordingly.
[0042] When comparing cooling rates, the rolling temperature of control group 6 was 320℃, and the cumulative true strain was... The value was 0.92, the target solution temperature was 1140℃, the axial online moving temperature homogenization time was 10s, and the quenching stage was changed to air mist reduced pressure cooling, reducing the overall cooling rate to 95℃ / s. Fine phases precipitated at the grain boundaries of this group, with an average grain size of 8.8μm and overlapping lattice points. The grain boundary ratio is 65.1%, the residual stress on the inner wall surface is -95 MPa, and the room temperature yield strength is... The pressure is 512 MPa, and the critical pitting temperature is 58.0℃; the pulsating fatigue test cycle is up to... Intergranular corrosion fatigue occurs at this time. After the cooling rate decreases, the residence time of the steel pipe in the sensitization temperature range increases, and fine phases precipitate at the grain boundaries, which corresponds to the decrease in the critical pitting temperature.
[0043] The above-mentioned test group underwent continuous treatments including warm rolling and cold drawing stepwise plastic deformation, high-frequency electromagnetic induction short-time solid solution, and asymmetric quenching, resulting in a lattice of overlapping positions. The grain boundary ratio is all above 65%, and the inner wall surface maintains a residual compressive stress state, with a room temperature yield strength. All pressures were no less than 520 MPa, and the critical pitting temperature measured according to ASTM G48 Method A was no less than 76 °C; under 300 MPa pulsating internal pressure, each test group withstood more than The following parameters were tested: undamaged after multiple cycles; symmetrical cooling; elimination of warm rolling; conventional long-term hot water quenching; solution temperature exceeding the test range; and reduced cooling rate. These parameters were considered in relation to residual stress, grain size, and lattice size at overlapping locations. The grain boundary ratio, critical pitting temperature, and pulsating fatigue life showed corresponding changes.
[0044] Example 3: This example selects a small-diameter, thick-walled super austenitic corrosion-resistant stainless steel pipe with an outer diameter of 6.35mm, an inner diameter of 3.00mm, and a wall thickness of 1.675mm as the manufacturing object. It is used to meet the requirements of intergranular corrosion resistance and fatigue spalling resistance in the ultra-high pressure common rail fuel injection system of internal combustion engines under high-pressure pulsating loads and long-term scouring conditions of chloride-containing acidic corrosive media. A dual process of vacuum induction melting and electroslag remelting is used to melt the alloy ingot. The chemical composition, by mass percentage, is controlled as follows: C 0.016%, Si 0.35%, Mn 1.20%, P 0.014%, S 0.002%, Cr 25.40%, Ni 22.30%, Mo 6.60%, N 0.25%, Cu 0.90%, with the balance being Fe and unavoidable impurities. Based on the pitting corrosion resistance equivalent formula... The calculated pitting resistance equivalent of the alloy is 51.18, of which... Indicates pitting resistance equivalent. , , The numbers represent the mass percentage content of chromium, molybdenum, and nitrogen in the alloy matrix, respectively. Forged round billets are heated to 1230℃ in a furnace and held for 55 min to eliminate dendrite segregation. They are then water-quenched to room temperature at a cooling rate exceeding 50℃ / s. Hot extrusion piercing produces an initial rough tube with an outer diameter of 25 mm and a wall thickness of 3.5 mm. The initial rough tube is preheated to 340℃ and fed into a two-roll periodic cold rolling mill for warm rolling. The reduction of area is controlled at 44.0%, reducing the diameter and wall thickness to a warm-rolled tube with an outer diameter of 15.8 mm and a wall thickness of 2.15 mm. This process forms interwoven dislocation slip bands and a high-density dislocation entanglement structure within the grains. After pickling with nitric acid and hydrofluoric acid, phosphating, and saponification lubrication, the warm-rolled tube undergoes three consecutive cold drawing processes at room temperature using a moving mandrel. The reduction of area for each pass is controlled at 22.5%, 20.8%, and 19.2%, respectively. The cumulative true strain is... Reaching 0.95, of which It represents the cumulative true strain of the stepped plastic deformation from warm rolling and cold drawing, which forms a deformation hardening structure inside the tube wall and stores the deformation energy required for subsequent recrystallization.
[0045] The cold-drawn steel pipe is uniformly fed into a multi-stage high-frequency electromagnetic induction heating coil at an axial moving speed of 0.15 m / s. A high-frequency alternating magnetic field is applied, causing the steel pipe to rapidly pass through the 600℃ to 1000℃ intermetallic phase sensitization temperature range at a heating rate of 180℃ / s and be heated to the target solid solution temperature of 1150℃. The axial online moving and homogenization time of the steel pipe at the target solid solution temperature of 1150℃ is controlled to be 9s, so that the nano-scale pre-precipitated carbide clusters and grain boundary intermetallic phases dissolve into the austenite matrix. At the same time, the deformation energy stored by the stepped plastic deformation of warm rolling and cold drawing causes discontinuous static recrystallization inside the pipe wall. The skin effect of high-frequency induction heating creates a radial temperature difference in the pipe wall section, with the outer wall temperature being higher than the inner wall temperature. After the steel pipe is removed from the induction heating coil, it enters a coaxially set air-water atomization cooling zone, where air-water mixture is sprayed synchronously into the inner hole and the outer wall. Asymmetric quenching is performed using a combined medium. The cooling medium injected into the inner hole of the steel pipe has a spray pressure of 1.5 MPa and a water-to-gas mass ratio of 1:3. The cooling medium sprayed onto the outer wall of the steel pipe has a spray pressure of 0.8 MPa and a water-to-gas mass ratio of 1:5. The jet direction of the medium nozzles on both the inner hole and the outer wall is reversed at a 55° angle to the axial movement direction of the steel pipe. The tangential shearing action of the jet eliminates the transient vapor film heat-insulating layer on the inner wall, making the cooling rate of the inner wall surface higher than that of the outer wall surface. The high kinetic energy cooling medium in the inner hole makes the transient cooling rate of the inner wall of the pipe reach 240℃ / s, and the average cooling rate of the entire steel pipe to below 400℃ reaches 215℃ / s. The surface structure of the inner hole cools and shrinks and solidifies before the outer wall. Subsequently, the outer wall applies radial and circumferential mechanical extrusion to the solidified inner hole surface during the late thermal shrinkage process, forming a residual compressive stress layer on the surface of the inner hole of the steel pipe.
[0046] After quenching, the steel pipe is subjected to cold reduction and sizing calibration under micro-tension conditions using a three-roll planetary mill. The outer diameter reduction is controlled at 0.9%, and the outer diameter of the steel pipe is calibrated to the target size of 6.35 mm. Subsequently, a mixed electrolyte of phosphoric acid and sulfuric acid is introduced into the inner hole of the steel pipe to perform pulsed electrochemical polishing. The 22 μm thick cold-worked modified layer on the surface of the inner hole is removed by anodic dissolution, while burrs and microcrack sources on the inner hole surface are also removed. The surface roughness of the inner hole of the treated steel pipe is [not specified]. The microstructure reached 0.09 μm, and the residual stress on the inner wall remained at a compressive stress state of -190 MPa. Microstructural analysis showed that the steel pipe matrix was a single-phase austenitic structure with no second-phase precipitation, and the average grain size was 8.2 μm, corresponding to a grain size meeting ASTM 11.2 grade. The coincident lattice points... The proportion of grain boundaries to the total grain boundary length reaches 70.2%, and the continuous random large-angle grain boundary network is broken, resulting in the specified room temperature plastic elongation strength of the finished steel pipe. Reaching 560MPa, tensile strength Reaching 890 MPa, elongation after fracture The measured hydraulic burst pressure reached 42.0%, with a measured pressure of 675 MPa. Under fatigue testing conditions with alternating pressure amplitudes from 0 to 300 MPa and a pulsating frequency of 20 Hz, the pressure... No crack initiation or leakage occurred during the second cycle. The critical pitting temperature measured according to ASTM G48 Method A reached 80.5℃. The above test results correspond to the ultra-high pressure operating requirements of the high-pressure common rail pipeline system for pressure bearing strength, resistance to high-frequency pulsating fatigue life, and resistance to multi-acidic corrosive media.
[0047] Example 4: This example combines Figures 1 to 2 This paper describes a method for preparing a high-performance high-pressure oil pipe, such as... Figure 1As shown, the preparation process includes steps S1 to S4. In step S1, the super austenitic corrosion-resistant stainless steel rough tube undergoes warm rolling and cold drawing in stages of plastic deformation, controlling the cumulative true strain to be no less than 0.85, constructing a deformation-hardening structure inside the tube wall to obtain the deformed steel tube. Then, in step S2, the deformed steel tube is fed into an induction heating coil and heated to the target solution temperature of 1120℃ to 1160℃ at a heating rate of 120℃ / s to 200℃ / s. The axial online moving temperature homogenization time at the target solution temperature is 8s to 15s, allowing the carbides and metal phases to dissolve into the austenitic matrix. Next, in step S3, the steel tube leaving the induction heating coil is introduced into a gas-water atomization cooling zone, and the temperature is further adjusted according to the induction heating process. After heating, the radial temperature difference between the outer wall temperature and the inner wall temperature of the pipe is higher. Asymmetric quenching is then performed by simultaneously injecting a gas-water mixture into the inner hole and the outer wall of the steel pipe. The pressure and water-gas mass ratio of the medium injected into the inner hole are controlled to be higher than those of the medium injected into the outer wall, so that the cooling rate of the inner wall surface is higher than that of the outer wall. The average cooling rate of the entire pipe to below 400℃ is not less than 180℃ / s. A residual compressive stress layer is formed on the inner hole surface by applying radial extrusion to the inner wall through the late thermal contraction of the outer wall. Finally, step S4 is performed to perform cold reduction and sizing dimension calibration on the quenched steel pipe and pulse electrochemical polishing on the inner hole of the steel pipe to remove the cold-worked hardened and modified layer on the inner hole surface to eliminate micro-defects on the inner surface.
[0048] like Figure 2 As shown, the super austenitic corrosion-resistant stainless steel tube billet casting and rough tube preparation process involves hot extrusion piercing to eliminate elemental dendrite segregation. Subsequently, controlled cumulative true strain is used to implement stepped plastic deformation through warm rolling and cold drawing, constructing a deformation-hardening structure and forming interwoven dislocation slip bands within the deformed tube wall. Next, the steel tube is fed into an induction heating coil for rapid solution treatment by controlling the heating rate. Under the action of axial online moving homogenization time, a homogenized solution state is achieved, allowing carbides and intermetallic phases to dissolve into the austenitic matrix and causing non-continuous phase formation within the tube wall. Static recrystallization continues; then, asymmetric quenching is carried out by spraying a gas-water mixture medium according to the radial temperature difference, so that the cooling rate of the inner wall surface is higher than that of the outer wall, and the radial extrusion of the inner wall is applied by the late thermal shrinkage of the outer wall, forming a residual compressive stress layer on the inner surface of the quenched steel pipe. Then, cold reduction and sizing dimension calibration and pulsed electrochemical polishing are carried out under micro-tension conditions to remove the cold-worked hardened and modified layer on the inner surface and eliminate micro-defects on the inner surface, so that the finished steel pipe has the properties of resistance to alternating pulsating fatigue and resistance to local corrosion.
[0049] Example 5: This example uses a super austenitic corrosion-resistant stainless steel pipe. Its chemical composition, by mass percentage, is as follows: carbon 0.018%, silicon 0.32%, manganese 1.25%, phosphorus ≤0.015%, sulfur ≤0.003%, chromium 20.45%, nickel 18.20%, molybdenum 6.25%, nitrogen 0.215%, copper 0.75%, with the remainder being iron and unavoidable accompanying impurities. The pitting corrosion resistance equivalent of the material is calculated using the following formula: ,in, This represents the dimensionless numerical value of pitting resistance equivalent. This represents the mass percentage of chromium. This represents the mass percentage of molybdenum. The value represents the mass percentage of nitrogen. Substituting the component values from this embodiment into the calculation, we obtain... It is 44.515.
[0050] In preparing high-pressure common rail tubing with an outer diameter of 6.00 mm and a wall thickness of 1.50 mm, a pure master alloy ingot is first obtained through vacuum induction melting combined with electroslag remelting. The ingot is then hot-forged into round steel, which is then hot-pierced to form a super austenitic corrosion-resistant stainless steel rough tube with an outer diameter of 38.00 mm and a wall thickness of 4.50 mm. Subsequently, the rough tube undergoes stepped plastic deformation through warm rolling and cold drawing, allowing the deformation formed during warm rolling and subsequent cold drawing deformation to continuously accumulate, thus accumulating true strain. The temperature is not less than 0.85, and a deformation hardening structure is formed inside the pipe wall. The deformed steel pipe is fed into the induction heating coil by axial online movement and heated to the target solid solution temperature of 1120℃ to 1160℃ at a heating rate of 120℃ / s to 200℃ / s. The axial online movement uniform temperature time at this temperature is controlled to be 8s to 15s, so that the carbides and the metal phase dissolve into the austenitic matrix.
[0051] After leaving the induction heating coil, the steel pipe enters the air-water atomization cooling zone, where a mixture of air and water is simultaneously sprayed onto the inner hole and outer wall for asymmetric quenching. The cooling medium sprayed into the inner hole has a spray pressure of 1.5 MPa and a water-to-air mass ratio of 1:3, while the cooling medium sprayed onto the outer wall has a spray pressure of 0.8 MPa and a water-to-air mass ratio of 1:5. The spraying directions of the inner hole and the outer wall are both reverse sprayed at an angle of 45° to 60° to the axial movement direction of the steel pipe. Utilizing the radial temperature difference between the outer wall and the inner wall after induction heating, and by increasing the cooling rate of the inner wall surface through the higher medium pressure and water-to-air mass ratio in the inner hole, the average cooling rate of the entire steel pipe to below 400°C is no less than 180°C / s. After the inner wall cools and shrinks before the outer wall, the late thermal shrinkage of the outer wall continues to apply radial compression to the inner wall, forming a residual compressive stress layer on the surface of the inner hole.
[0052] After asymmetric quenching, the steel pipe is cold-reduced and sized using a three-roll planetary mill, with the outer diameter reduction controlled between 0.5% and 1.2%. Subsequently, a mixed electrolyte of phosphoric acid and sulfuric acid is introduced into the inner bore of the steel pipe for pulsed electrochemical polishing. This anodic dissolution removes the 15μm to 25μm work-hardened altered layer on the inner bore surface and eliminates microscopic defects, resulting in a smoother inner bore surface. No larger than 0.15μm.
[0053] A multi-pass cold drawing-continuous roller hearth atmosphere furnace treatment route was set up for comparison and verification. This route directly performs multi-pass cold drawing on the rough tube, with the cross-sectional deformation rate controlled between 25% and 35% in each pass. A bright intermediate annealing under hydrogen protection is used between passes, with annealing temperatures ranging from 1080℃ to 1100℃ and holding time calculated at 1.5 min per millimeter of tube wall thickness. The tube is then formed into the target specification after four passes of cold drawing. Subsequently, the formed tube is placed in a continuous roller hearth atmosphere furnace for solution heat treatment at a heating temperature of 1180℃ and a soaking time of 4 min. After treatment, it is continuously quenched to room temperature by high-pressure fluid jet cooling at a rate greater than or equal to 60℃ / s, and then subjected to a process exceeding 65℃. The second-phase precipitation sensitive temperature zone is from 0℃ to 900℃. Multiple sets of high-power, high-frequency induction heating coils are installed inside the continuous roller hearth atmosphere furnace. After the tube is preheated to 800℃ in the furnace chamber, it passes through the induction coil section at a speed of 0.15m / s. Under the action of the induction coil, the temperature rises to 1180℃ at a rate greater than 150℃ / s and is maintained for a short period of 10s for temperature uniformity. This is followed by high-pressure fluid asymmetric jet quenching. The total holding time of 4 minutes includes 3.8 minutes of slow preheating and holding in the furnace chamber and 0.2 minutes of rapid heating and temperature uniformity in the induction coil section. The internal hole post-treatment of this comparative route uses extrusion honing and electrochemical passivation polishing to reduce the surface roughness of the internal hole. Reduced to below 0.15μm.
[0054] Based on the above comparative verification route, four sets of comparative sample tubes were prepared. Comparative Example 1 was a low-molybdenum and low-nitrogen comparative group, with the molybdenum content reduced to 4.20% and the nitrogen content reduced to 0.110%, while the remaining components and preparation process were consistent with the comparative verification benchmark sample. Comparative Example 2 was an upper-limit chromium-molybdenum comparative group, with the chromium content increased to 24.50%, the molybdenum content increased to 7.80%, and the nitrogen content increased to 0.320%, while the remaining components and preparation process were consistent with the benchmark sample. Comparative Example 3 kept the chemical composition of the tube unchanged, and after solution heat treatment, conventional air cooling was used, with an average cooling rate of 8.5℃ / s measured in the range of 650℃ to 900℃. Comparative Example 4 also kept the chemical composition of the tube unchanged, but the solution heat treatment heating temperature was reduced to 1050℃, and after exiting the furnace, a fluid jet cooling rate of greater than or equal to 60℃ / s was maintained.
[0055] For the steel pipes produced by the main preparation route, the critical pitting temperature was tested using ASTM G48 Method A, and pulsating fatigue was evaluated using alternating internal pressure from 0 to 300 MPa and a pulsating frequency of 20 Hz. The comparative verification sample pipes were also tested under the original comparative conditions: room temperature tensile properties were tested according to GB / T228.1 at 23°C; the austenite average grain size was evaluated using the intercept method according to ASTM E112; the critical pitting temperature was tested according to ASTM G48 Method C, with the test medium being a mixed aqueous solution of 6% ferric chloride and 1% hydrochloric acid; a hydraulic burst test was performed on the finished pipe sections according to GB / T241, and a high-frequency pressure pulse fatigue life test was conducted at a working pressure of 2800 bar, with the pulse frequency set to 15 Hz, to induce leakage or reach the critical temperature. The failure to fracture in the second cycle was used as the termination condition for the fatigue test.
[0056] Under these comparative conditions, the reference specimen was measured to have the specified plastic elongation strength. The tensile strength is 468 MPa. The strength is 865 MPa, and the elongation after fracture is... The content was 45.5%, and the grain size grade was 9.0. No abnormalities were observed at the grain boundaries of the austenite matrix under 1000x magnification metallographic microscopy and transmission electron microscopy. The phase or nitride precipitates have a critical pitting temperature of 87.5℃, and the measured hydraulic burst pressure is 385MPa, reaching [a certain value] under a 2800bar pressure pulse. After one cycle, the tube body remained intact without any cracks.
[0057] Comparative Example 1: Measured Specified Plastic Tensile Strength The tensile strength is 365 MPa. The strength is 710 MPa, and the elongation after fracture is... The percentage was 48.0%, the grain size was grade 8.0, and the critical pitting temperature dropped to 52.5℃; after 2800 bar pressure pulse cycling to At this point, fatigue microcracks initiated at the micro-pitting corrosion initiation site on the inner wall, and early leakage occurred. In Comparative Example 2, through-type longitudinal microcracks were generated during the third pass of hot piercing and cold drawing, and large-sized brittle particles precipitated in the as-cast matrix. phase and The phase exhibits a significant decrease in hot working plasticity, and the room temperature impact absorption energy of the finished sample is below 15J.
[0058] Comparative Example 3: Measured Specified Plastic Elongation Strength The tensile strength is 435 MPa. The strength is 820 MPa, and the elongation after fracture is... The content decreased to 28.5%, with a grain size grade of 8.5; a continuous network of chromium-rich molybdenum was detected at the grain boundaries. Brittle phase and Precipitation occurred, with a critical pitting temperature of 45.0℃ and a hydraulic burst pressure of 290MPa, under pressure pulse cycling at 2800 bar. Brittle cracking occurred along the grain boundaries at this time, and the specified plastic elongation strength was measured in Comparative Example 4. The tensile strength is 440 MPa. The strength is 830 MPa, and the elongation after fracture is... The percentage was 32.0%; the solution temperature did not reach the solidus kinetic threshold for complete solid solution diffusion of alloying elements, and there were still undissolved primary intermetallic compounds in the matrix. The critical pitting temperature was 60.0℃, and the pulse fatigue life was [missing information]. The above comparison results correspond to different compositions and different heat treatment and cooling conditions. In the comparative verification route, when chromium, nickel, molybdenum and nitrogen elements are used in the ratio given in this embodiment and combined with solid solution rapid cooling of greater than or equal to 60℃ / s, the precipitation of chromium-molybdenum brittle phase at the grain boundaries is suppressed, the matrix maintains a single-phase austenitic structure, and exhibits corresponding tensile, pulsating fatigue and acid corrosion resistance.
[0059] Example 6: In this example, a small-diameter, thick-walled super austenitic corrosion-resistant stainless steel pipe with an outer diameter of 6.35 mm, an inner diameter of 3.00 mm, and a wall thickness of 1.675 mm was selected as the preparation object to verify the microstructural stability of the ultra-high pressure common rail fuel injection pipeline under conditions of high cumulative deformation energy storage and high alloy composition solid solution. The alloy ingot was smelted using a combination of vacuum induction melting and electroslag remelting. The chemical composition, by mass percentage, included: C 0.015%, Si 0.45%, Mn 1.40%, P 0.012%, S 0.002%, Cr 25.85%, Ni 22.80%, Mo 7.10%, N 0.27%, Cu 1.10%, with the balance being Fe and unavoidable impurities. Based on the pitting resistance equivalent formula... The calculated pitting resistance equivalent of the alloy is 53.60, of which... Indicates pitting resistance equivalent. , , The numbers represent the mass percentage content of chromium, molybdenum, and nitrogen in the alloy matrix, respectively. The forged round billet was heated to 1240℃ in a furnace and held for 60 minutes to eliminate dendritic segregation caused by high molybdenum and chromium content. It was then water-quenched to room temperature at a cooling rate exceeding 50℃ / s. The billet was then hot-extruded and pierced to produce an initial rough tube with an outer diameter of 25mm and a wall thickness of 3.5mm. The initial rough tube was preheated to 350℃ and then fed into a two-roll periodic cold rolling mill for warm rolling, resulting in a reduced cross-sectional area. The shrinkage rate was controlled at 45.0%, reducing the diameter and wall thickness to a warm-rolled tube with an outer diameter of 15.5 mm and a wall thickness of 2.10 mm. This process formed interwoven dislocation slip bands and a high-density dislocation entanglement structure within the grains. After pickling with nitric acid and hydrofluoric acid, phosphating, and saponification lubrication, the warm-rolled tube underwent three consecutive cold drawing processes at room temperature using a moving mandrel. The area reduction rates for each pass were controlled at 24.5%, 22.0%, and 20.5%, respectively, maximizing the cumulative true strain of the stepped plastic deformation from warm rolling and cold drawing. It reached 1.05, of which It represents the cumulative true strain of the stepped plastic deformation of warm rolling and cold drawing, and forms a deformation hardening structure inside the tube wall, so that the deformation energy storage is distributed in the lattice distortion region of the tube wall cross section.
[0060] The cold-drawn steel pipe is uniformly fed into a multi-stage high-frequency electromagnetic induction heating coil at an axial moving speed of 0.15 m / s. A high-frequency alternating magnetic field is applied, heating the steel pipe to the target solution temperature of 1160℃ at a heating rate of 200℃ / s. At 1160℃, the axial online moving and homogenization time is controlled to 8s, allowing nanoscale pre-precipitated carbide clusters and intergranular metal phases to dissolve into the austenite matrix. Simultaneously, the deformation energy stored by the preceding stepwise plastic deformation causes discontinuous static recrystallization inside the pipe wall. The average recrystallized grain size is controlled to 7.5μm, corresponding to a grain size of ASTM 11.5. The skin effect of high-frequency induction heating creates a radial temperature difference in the pipe wall section, with the outer wall temperature higher than the inner wall temperature. After the steel pipe is removed from the induction heating coil, it enters a coaxially set air-water atomization cooling zone, where air is sprayed synchronously onto the inner hole and the outer wall. Asymmetric quenching is performed using a mixture of air and water. The cooling medium injected into the inner hole of the steel pipe has a spray pressure of 1.5 MPa and a water-to-air mass ratio of 1:3. The cooling medium injected onto the outer wall of the steel pipe has a spray pressure of 0.8 MPa and a water-to-air mass ratio of 1:5. The jetting directions of the media nozzles on both the inner hole and the outer wall are reversed at a 60° angle to the axial movement direction of the steel pipe. The tangential shearing action of the jet eliminates the transient vapor film heat-insulating layer on the inner wall, making the cooling rate of the inner wall surface higher than that of the outer wall surface. The steel pipe cools from 1160℃ to 370℃ in 3.36s, and the average cooling rate of the entire pipe below 400℃ reaches 235.1℃ / s. The surface structure of the inner hole cools and shrinks before the outer wall. Subsequently, the outer wall applies radial and circumferential mechanical extrusion to the already shaped inner hole surface during the late thermal shrinkage process, forming a residual compressive stress layer on the surface of the inner hole of the steel pipe.
[0061] After quenching, the steel pipe is subjected to cold reduction and sizing calibration under micro-tension conditions using a three-roll planetary mill. The outer diameter reduction is controlled at 1.2%, and the outer diameter of the steel pipe is calibrated to the target size of 6.35 mm. Subsequently, a mixed electrolyte of phosphoric acid and sulfuric acid is introduced into the inner hole of the steel pipe to perform pulsed electrochemical polishing. The 25 μm thick cold-worked modified layer on the surface of the inner hole is removed by anodic dissolution, while burrs and microcrack sources on the inner hole surface are also removed. The surface roughness of the inner hole of the treated steel pipe is [not specified]. The thickness reaches 0.08 μm, and the residual stress on the inner wall remains at a compressive stress state of -215 MPa. Microstructural analysis shows that the steel pipe matrix has a single-phase austenitic structure with no second-phase precipitation, and low-energy coincidence lattice points. The proportion of grain boundaries to the total grain boundary length reaches 71.5%, and the continuous random large-angle grain boundary network is broken. The room temperature specified plastic elongation strength of the finished steel pipe is affected. Reaching 575MPa, tensile strength Reaching 905 MPa, elongation after fracture The hydraulic burst pressure reached 41.5%, with a measured value of 685 MPa. Under fatigue testing conditions with alternating internal pressure from 0 to 300 MPa and a pulsating frequency of 20 Hz, the pressure... No crack initiation or leakage occurred during the second cycle. The critical pitting temperature, measured according to ASTM G48 Method A, reached 82.5℃. The corresponding pressure resistance, high-frequency pulsating fatigue life, and resistance to multi-acidic corrosive media meet the working requirements of the ultra-high pressure common rail fuel injection pipeline.
[0062] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for manufacturing a high-performance high-pressure oil pipe, characterized in that, Includes the following steps: Step S1: Perform warm rolling and cold drawing stepwise plastic deformation on the super austenitic corrosion-resistant stainless steel rough tube, control the cumulative true strain to be not less than 0.85, construct a deformation hardening structure inside the tube wall, and obtain the deformed steel tube. Step S2: The deformed steel pipe is fed into an induction heating coil and heated to the target solution temperature of 1120°C to 1160°C at a heating rate of 120°C / s to 200°C / s. The axial online moving temperature uniformity time at the target solution temperature is 8s to 15s, so that the carbides and metal phases dissolve into the austenitic matrix. Step S3: The steel pipe leaving the induction heating coil is introduced into the gas-water atomization cooling zone. Based on the radial temperature difference between the outer wall temperature and the inner wall temperature after induction heating, a gas-water mixed medium is simultaneously sprayed into the inner hole and the outer wall of the steel pipe to carry out asymmetric quenching. The pressure of the medium sprayed into the inner hole and the water-gas mass ratio are controlled to be higher than the pressure of the medium sprayed onto the outer wall, so that the cooling rate of the inner wall surface is higher than the cooling rate of the outer wall, and the average cooling rate of the whole to below 400℃ is not less than 180℃ / s. A residual compressive stress layer is formed on the inner hole surface by applying radial extrusion to the inner wall through the late thermal contraction of the outer wall. Step S4 involves performing cold reduction and sizing calibration on the quenched steel pipe and pulse electrochemical polishing on the inner hole of the steel pipe to remove the cold-worked hardened and modified layer on the surface of the inner hole and eliminate micro-defects on the inner surface.
2. The method for preparing a high-performance high-pressure oil pipe according to claim 1, characterized in that, In step S1, the total reduction of area of the stepped plastic deformation is 65% to 85%, and includes the following sub-processes: Step S11, the super austenitic corrosion-resistant stainless steel rough tube is preheated to 280°C to 350°C and subjected to two-roll cyclic warm rolling, with a reduction of area of 35% to 45%; Step S12, the steel tube after warm rolling is subjected to surface pickling, phosphating and saponification lubrication treatment; Step S13, the steel tube is subjected to 2 to 3 passes of floating mandrel cold drawing at room temperature, with the reduction of area per pass controlled at 18% to 25%, forming interwoven dislocation slip bands inside the tube wall.
3. The method for preparing a high-performance high-pressure oil pipe according to claim 1, characterized in that, Before step S1, there are also billet casting and rough tube preparation processes: alloy ingots are cast using a combination of vacuum induction melting and electroslag remelting; the alloy ingots are heated to 1200℃ to 1240℃ and held for 45min to 60min for high-temperature homogenization treatment; then, they are water quenched to room temperature at a cooling rate of not less than 50℃ / s, and hot extrusion piercing is used to produce super austenitic corrosion-resistant stainless steel rough tubes.
4. The method for preparing a high-performance high-pressure oil pipe according to claim 1, characterized in that, In step S2, the steel pipe passes through the induction heating coil at a uniform axial moving speed of 0.15 m / s. After solution treatment, the average grain size of recrystallization inside the austenitic matrix is controlled between 7.5 μm and 12.0 μm, corresponding to a grain size of ASTM grade 10.0 to 11.
5.
5. The method for preparing a high-performance high-pressure oil pipe according to claim 1, characterized in that, The process parameters for asymmetric quenching in step S3 are as follows: the injection pressure of the cooling medium injected into the inner hole is 1.5 MPa, and the water-to-air mass ratio is 1:3; the injection pressure of the cooling medium injected towards the outer wall is 0.8 MPa, and the water-to-air mass ratio is 1:5; and the injection directions of the cooling medium injected towards the inner hole and the outer wall are both reverse injection at an angle of 45° to 60° with the axial movement direction of the steel pipe.
6. The method for preparing a high-performance high-pressure oil pipe according to claim 1, characterized in that, After processing in steps S2 and S3, the lattice of overlapping positions in the microstructure of the steel pipe The proportion of grain boundaries to the total grain boundary length is not less than 65%, and a residual compressive stress layer is formed on the surface of the inner hole of the steel pipe.
7. The method for preparing a high-performance high-pressure oil pipe according to claim 1, characterized in that, In step S4, the cold reduction and sizing dimension calibration is performed using a three-roll planetary mill, with the outer diameter reduction controlled between 0.5% and 1.2%; the pulse electrochemical polishing uses a mixed electrolyte of phosphoric acid and sulfuric acid to remove the surface layer of the inner hole of the steel pipe with a single-sided thickness of 15μm to 25μm.
8. The method for preparing a high-performance high-pressure oil pipe according to claim 1, characterized in that, After step S4, the surface roughness of the inner hole of the steel pipe is... The pitting depth is no greater than 0.15 μm, the residual stress on the inner wall is in a compressive stress state or a tensile stress state with a value no greater than 30 MPa, and the critical pitting temperature measured according to ASTM G48 Method A is no less than 76 °C.
9. The method for preparing a high-performance high-pressure oil pipe according to claim 1, characterized in that, The room temperature yield strength of the finished steel pipe It can withstand 10,000,000 cycles of pulsating fatigue load with an alternating internal pressure of 0 to 300 MPa and a frequency of 20 Hz without cracking or leakage, and the hydraulic burst pressure is not less than 650 MPa.
Citation Information
Patent Citations
Manufacturing method of super austenitic stainless steel seamless tube
CN104826890A